Bordetella pertussis isolates in Finland after acellular vaccination : serotype change and biofilm formation - Niinikoski, Vili; Barkoff, Alex-Mikael; Mertsola, Jussi; He, Qiushui (Elsevier, 2025)
Objectives: In Finland, whole cell pertussis vaccine (wP) was introduced in 1952 and was replaced by acellular pertussis vaccine (aP) without fimbrial (FIM) antigen in 2005. We aimed to analyse the changes in serotypes of circulating Bordetella pertussis before and after acellular vaccination and to explore the relationship between biofilm formation and serotype diversity after the introduction of aP vaccine.
Methods: Serotyping of 1399 B. pertussis isolates collected at the Finnish National Reference Laboratory for Pertussis and Diphtheria in Turku, Finland, from 1974 to 2023 was performed by slide agglutination or indirect ELISA. Of 278 isolates collected after 2005, 53 were selected, genotyped for fim3 and fim2 alleles, and tested for biofilm formation. The selection criteria included maintaining a relatively equal distribution of isolates per time interval, ensuring approximately a 50:50 ratio of FIM2 (N = 26) and FIM3 (N = 27) serotypes. The reference strain Tohama I was used as a control.
Results: During the wP era, the majority of circulating B. pertussis exhibited the FIM2 serotype. However, FIM3 strains have appeared since 1999 and become prevalent. After the implementation of aP vaccines, the distribution of serotypes has exhibited substantial variability. FIM3 isolates displayed an enhanced biofilm formation compared to FIM2 isolates (Geometric mean value (95% CI): 0.90 (0.79-1.03) vs. 0.75 (0.65-0.85); p < 0.05). Of the 27 FIM3 isolates, 8 harboured fim3-1 and 19 fim3-2 alleles. FIM3 isolates with fim3-2 allele were significantly associated with increased biofilm formation when compared to those with fim3-1 (1.07 (0.96-1.19) vs. 0.61 (0.52-0.72); p < 0.0001).
Conclusion: Following the implementation of aP vaccines, the distribution of serotypes in Finland has exhibited substantial variability. FIM3 isolates with the fim3-2 allele displayed an enhanced biofilm formation capability compared to FIM2 isolates.